ARCHETYPES SYMBOLISING ATHENA’S PERSONALITY DEVELOPMENT IN THE WITCH OF PORTOBELLO - Yohana Gabriella Nanda Kristiani; Priyatno Ardi (Elite : English and Literature Journal, 2019)
Novels often use symbols to voice their authors’ opinions about individuals’ personalities. One type of symbols used is an archetype. This study aims to investigate the archetypes of a character named Athena in Paulo Coelho’s The Witch of Portobello (2008). The researchers employed a library study to conduct this study. The results show that there are six archetypes, namely Pallas Athena, the Virgin, the Martyr, the Saint, the Witch, and Hagia Sofia. The archetypes portraying her initial personality are Pallas Athena, the Virgin, the Martyr, and the Saint. The archetypes depicting Athena’s developed personality are the Saint, the Witch, and Hagia Sophia. In conclusion, these archetypes are able to symbolise Athena’s personality development.ABSTRAKNovel sering menggunakan symbol-simbol untuk menyampaikan gagasan penulisnya tentang  kepribadian seseorang. Salah satu simbol yang digunakan ialah arketipe. Penelitian ini bertujuan untuk meneliti arktipe seorang karakter bernama Athena dalam novel yang ditulis oleh Paulo Coelho, yang berjudul The Witch of Portobello (2008). Penulis menggunakan kajian pustaka dalam penelitian ini. Hasil penelitian ini menunjukkan bahwa ada enam arketipe yang dimiliki Athena, yaitu Pallas Athena, Perawan Maria, Martir, Orang Kudus, Penyihir dan Hagia Sofia. Arketipe-arketipe yang menggambarkan kepribadian awal Athena adalah Pallas Athena, Perawan Maria, Martir dan Orang Kudus. Arketipe-arketipe yang menggambarkan perkembangan kepribadian Athena adalah Orang Kudus, Penyihir dan Hagia Sofia. Kesimpulannya, arketipe-arketipe dalam novel tersebut ini menyimbolkan perkembangan kepribadian Athena.Kata kunci: arketipe, perkembangan kepribadian, Athena.